Interval analysis of repetitive denervation potentials of human skeletal muscle. Issue 6 (December 1972) - Conrad, B.; Sindermann, F.; Prochazka, V. J.
Abstract : Interval analyses of denervation potentials (fibrillation-potentials and positive sharp waves) in human skeletal muscles were performed using a DEC PDP-12 computer. Extremely small differences between consecutive intervals (usually less than 1%) and slow up and down drifts in the spontaneous discharge frequency were found to be characteristic of repetitive denervation potentials. These two findings are safe criteria for the clinical diagnosis of denervation and they may be superior to the more commonly used criteria based upon the shapes, amplitudes, and durations of the potentials. Physiological data from the literature as well as hypotheses relating to spontaneous activity are reviewed. Generator potentials across the muscle fibre membrane, lowered firing threshold, and constant-sized after-potentials are considered the basic factors relevant to spontaneous and rhythmical firing and to the slow drift observed in the firing frequency.